Synthesis of bio-polyols by epoxide ring opening reaction with H2O as a reagent - Thuy, Nguyen Thi; Duc, Vu Minh; Liem, Nguyen Thanh (Vietnam Journal of Chemistry, 2017)
The different nucleophilic reagents have been using in epoxide ring opening reactions among which water is the most preferable. At first, the epoxide group must be protonated by water in the presence of H2SO4 as catalyst. The successful epoxide ring opening reaction of epoxidized soybean oil (ESO) by water in the H2SO4 environment was verified by FTIR and H-NMR spectroscopy. The effect of reaction parameters like the amount of reagents, catalyst, temperature and time of a polyol synthesis were studied through the hydroxyl and oxirane oxygen content of product. Moreover, the impact of the parameters on the correlation P/E was determined by comparing a hydroxyl group formation to an epoxide group consumption. When the hydroxylation reaction was carried out with ESO:H2O mole ratio of 1:15; in 8 wt.% H2SO4; at temperature of 70 oC and in 5 hours, the hydroxyl content of 358.51 mgKOH/g of the obtained product was achieved. Keywords. Epoxidized vegetable oil, biopolyol, epoxide ring-opening, epoxidized soybean oil.